Thermal analysis and microscopic characterisation of the Al-20%Mg2Si in-situ composite - Farahany, Saeed (2012)
Al-Mg2Si is an in-situ composite composed of aluminium, magnesium and silicon elements. The reinforcement of Mg2Si crystal structure occurs due to very small solid solubility of Si into Mg. This material is becoming an attractive candidate to manufacture most of industrial products especially automotive and aerospace components. In this research paper, four different phase reactions were detected under slow solidification of base alloy by computer-aided cooling curve thermal analysis (CA-CCTA). Backscattered electron (BSE) imaging and elemental mapping revealed that those phase evolutions corresponded to the formation of primary Mg2Si reinforcement particle, Al-Mg2Si eutectic, Si eutectic and Iron intermetallic respectively.